Core competencies of a global oil and gas company: a qualitative analysis - Krishnan, Deven; Islam, Rafikul (Australian Business and Management Publications, 2019)
The main objective of the paper is to identify core competencies, understand how they benefit the organisation, as well as to unveil the development of core competencies in an oil and gas company in Malaysia. Semi-structured interviews were purposively conducted with ten experienced executive officers from an oil and gas company to solicit information about the company’s core competencies, how core competencies have helped the company, and how the company develops its core competencies. The study not only identified core competencies, but also shed light on the benefits of core competencies and revealed the development of core competencies in an oil and gas company in Malaysia. Of utmost importance is the finding that there is support for the benefit of developing core competencies in the oil and gas industry, as shown by the interview findings and the literature. The studies related to core competencies are still lacking in the oil and gas industry. Hence, it is expected that the present study findings can help organisations understand if their strategic initiatives and plans are heading towards the right direction.